(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
Currently, there is a growing demand worldwide for the use of hydro units with simple designs, compact sizes, high efficiency, and minimal environmental impact in electricity production. As with all types of machines, mechanical transmissions play a crucial role in ensuring high efficiency in the design of hydro units. This article presents several calculation schemes for selecting drives for hydromachines designed for natural water flows and recommends a rational drive design.